Vibration Modes of the Cello Tailpiece - FOUILHE, Eric; GOLI, Giacomo; HOUSSAY, Anne; STOPPANI, George (Archives of Acoustics, 2011)
The application of modern scientific methods and measuring techniques can ex- tend the empirical knowledge used for centuries by violinmakers for making and adjusting the sound of violins, violas, and cellos. Accessories such as strings and tailpieces have been studied recently with respect to style and historical coherence, after having been somehow neglected by researchers in the past. These fittings have played an important part in the history of these instruments, but have largely disappeared as they have been modernised. However, the mechanics of these accessories contribute significantly to sound production in ways that have changed over time with different musical aesthetics and in different technical contexts. There is a need to further elucidate the function and musical contribution of strings and tailpieces. With this research we are trying to understand the modifications of the cello’s sound as a consequence of tailpiece characteristics (shape of the tailpiece and types of attachments). Modal analysis was used to first investigate the vibration modes of the tailpiece when mounted on a non-reactive rig and then when mounted on a real cello where it can interact with the modes of the instrument’s corpus. A preliminary study of the effect of the tailpiece cord length will be presented.